The Use of Pre-Reading Strategy in Teaching Reading Comprehension - Mila Silvia Febrianti; Moh Nur Arifin; Tatu Siti Rohbiah (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2022)
This study aims to find out the kinds of pre-reading strategy used by the teacher and how to apply pre-reading strategy in teaching reading comprehension. The formulated problems of this study were: (1) What kinds of pre-reading strategies are used by the teacher? (2) How is a pre-reading strategy applied for teaching reading comprehension? This research was conducted through qualitative research. The type of research was specifically a case study. The participants of this study were 33 students and one English teacher at the ninth-grade students of SMPN 1 Mancak, Serang. Observations and interviews were used to collect the data. The findings of the study indicated the teachers apply several kinds of pre-reading strategies, such as brainstorming, pre-teaching vocabulary, pre-questioning, and previews. There are some students who have barriers in reading comprehension due to lack of vocabulary. So, the teacher applied pre-teaching vocabulary to increase the students’ vocabulary. Besides, there are those who have trouble applying the kind of pre-reading strategy known as pre-questioning. Pre-questioning seems to be the most difficult to apply in Junior High School student. On the other hand, other kinds can assist students in determining a topic sentence of the text.